11th International Workshop on Cellular Neural Networks and their Applications CNNA 2008 - First Call for papers (IEEE circuits and systems magazine (New York, N.Y. 2001), 2007)
Prospective authors are requested to submit new, unpublished manuscripts for inclusion in the upcoming event described in this call for papers.